Total Harmonic Distortion of Bidirectional AC-DC Microgrid System for PV Application - Ojaswini Nag,Dr. Nand Kishore (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
For the increasing energy demand and continuously decreasing rate of fossil fuel the Hybrid AC/DC Microgrid system with renewable energy sources (RES) is the one of the sustainable solution. The Hybrid AC/DC Microgrid system improves the power flow in distribution network and reduces power losses in transmission lines. In the Hybrid AC/DC Microgrid system multiple reverse conversion operation reduces with efficient bidirectional power converter is the another preferable solution. Similarly to increase the system reliability extendable voltage range battery system should be utilized. The proposed hybrid Microgrid operates in grid-tied or isolated mode. AC sources and loads are connected to AC network, whereas DC sources and loads are connected to DC network. Uncertainty and intermittent characteristics of wind speed, solar irradiation level, ambient temperature and load are additionally considered in the system model and operation.